Efeito de inibidores da síntese (avg) e da ação(1-mcp) do etileno em pêssegos cv. eldorado - Mello, Anderson Machado de (2005)
The objective of this work was to evaluate the effect of the application of aminoethoxyvinylglycine (AVG) and 1-methylcyclopropene (1-MCP) on the quality of Eldorado peaches during cold storage. The treatments were combinations among AVG ([S]-Trans-2-Amino-4-(2-aminoethoxy)-3-butenoic acid hydrochloride) preharvest sprays on the trees in different dates (0, 15 and 21) days before harvest, and 1000ppb of 1-MCP applied in postharvest. The AVG concentrations were 0, 125, 187.5 and 249.0 g ha-1. The fruit were stored during 3 weeks at 0°C plus 5 days at 20ºC. According to the results the AVG sprays did not show effect on the quality of fruit considering periods of application and concentrations. However 1-MCP treatment was efficient in the maturation control and maintenance postharvest of qualities: pulp firmness, acidity, background color, ethylene production and respiration.